The educational attainment of the second generation in Germany: social origins and ethnic inequality - Cornelia Kristen; Nadia Granato (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2007)
With the German Microcensus we study the second generation's educational attainment in Germany focusing on the descendants of classic labour migrants. Our results show that educational outcomes in terms of attending or completing the highest schooling track leading to the Abitur considerably vary among different ethnic groups. Second generation young adults, in particular Turks and Italians, experience pronounced disadvantages in comparison to their German peers. The central question in this context is to what extent ethnic stratification in the German school system is related to educational and social background. Our findings suggest that ethnic disadvantages primarily result from social rather than from specific ethnic inequalities, since initial differences in the chances of attaining the Abitur disappear after considering educational and social origin, the only exception being Italian young adults.
Keywords: I21; J61; J62; 330; ausländische Kinder; zweite Generation; Schulleistung; Schulabschluss; soziale Herkunft - Auswirkungen; Bildungsniveau; ausländische Jugendliche; Abitur - Quote; ethnische Gruppe - Auswirkungen; Mikrozensus; Bildungschancengleichheit; Türken; Italiener; Benachteiligung; benachteiligte Jugendliche; Minderheiten; Jugoslawen; Griechen; Spanier; Portugiesen; Einwanderer; geschlechtsspezifische Faktoren; Westdeutschland; Bundesrepublik Deutschland; Bildungsniveau; Jugendliche; Migranten; Ausländer; Ethnische Gruppe; Familiensoziologie; Türken; Italiener; Deutsche; Deutschland